Factors influencing employee job satisfaction at commercial Banks in Bangladesh - Haque, A. K. M. Ahasanul; Wan Nasir, Zaireena; Anis, Md. Zohurul; , Md. Faisal-E-Alam; Sarkar, Md. Atiqur Rahman (2019)
Job satisfaction is a common issue in banks throughout the world. For the past couple of decades, various studies endeavored to investigate the relative significance of understanding job satisfaction. The employer of banks has given importance on job satisfaction of employees in order to remain competitive. In the perspective of Bangladesh, the present scenario of employees’ job satisfaction is appalling. The employers of commercial banks have little attention toward the job satisfaction of their employees. Thus, it is necessary to make sure and improve job satisfaction of employees to benefit employees and organization. This study has been conducted with the aim of identifying factors of job satisfaction in commercial banks. Employees from commercial banks have been selected as respondents on the basis of simple random sampling technique. Initially, reliability test has been conducted in determining the factors of job satisfaction. Then, factor analysis has been carried out to identify the factors by analyzing data and interpret the findings. Five factors have been found from the factor analysis namely managerial support, training and career development, salary and benefits, work environment and hour, and coworker relationship. The cumulative variance of these five factors is 70.186% which indicates that five factors are mostly influential on job satisfaction of employees in commercial banks. In this way, commercial banks are able to increase employees’ job satisfaction and employees’ inspiration by working on these five factors for achieving its ultimate success.